Os feminismos de segunda onda: a união das mulheres cearenses (1979-1985) - Silva, Sarah Pinho da (2020)
The research, here presented, sought to understand the formation of the União das Mulheres Cearenses-UMC (Union of Women of Ceará), in 1979, considered the first feminist entity, in Ceará, during the period of the Brazilian Military Dictatorship, as well as the period of the emergence of Second Wave feminisms in Brazil. In the process of dismantling leftist organizations, persecutions, prisons, tortures and deaths, feminisms emerged in the country, combining the struggle of women with the fight against the military dictatorship and class struggle. UMC was formed at this juncture and sought to dialogue with general and specific agendas, based on the link with left-wing political parties. From the theoreticalmethodological scope, which consisted of the bibliographic survey – the use of documentation from the National Information System-SNI; documents produced by the UMC, Statute and Resolution of the I Congress of the Woman of Ceará; oral testimonies – the emergence, formation, development and divisions within the entity were narrated, internal conflicts, the repercussions of the movement and the surveillance of security agents on the institution, disagreements and disruptions that existed at UMC were analyzed . Along this path, the multiplicity surrounding the organization and the challenges it encountered to remain hegemonic ahead of feminisms in Ceará were analyzed. In this way, UMC became a feminist entity, despite the criticisms and internal disagreements, among the militants themselves, established itself in the memory of many women who experienced Second Wave feminisms in Ceará, constituting a feminist political identity a from the entity.